Perbandingan Pijat Oksitosin Dan Konsumsi Daun Kelor Terhadap Peningkatan Produksi Asi Di Klinik Salsabila Mom & Baby Spa Kecamatan Periuk Kota Tangerang - Shafa Salsabila Nurdin; Resi Galaupa (Jurnal Keperawatan Muhammadiyah, 2024)
Exclusive breastfeeding is still low, efforts to overcome this are by increasing the quality and quantity of breast milk, including giving oxytocin massage which increases the hormone oxytocin which can calm the mother so that breast milk comes out automatically and consuming Moringa leaves because they contain phytosterols which can increase breast milk production. Purpose of writing: To determine the comparison of oxytocin massage and consumption of Moringa leaves on increasing breast milk production at the Salsabila Mom & Baby SPA Clinic, Periuk District, Tangerang City in 2023. Research Method: quasi experimental design with pretest-posttest design with control group design. The sample of mothers breastfeeding 3 days after giving birth whose breast milk production was not smooth in December 2023 was 44 samples using the accidental sampling technique. Bivariate analysis uses Paired Samples T-Test and Independent T-test. Research Results: The results of the univariate research were the average breast milk production from giving oxytocin massage before and after 7.00, the average breast milk production when giving Moringa leaves before and after was 4.41 and after 7.91. The results of bivariate research on breast milk production on giving oxytocin massage (p value = 0.000) and giving moringa leaves (p value = 0.000), the difference in the effect of giving oxytocin massage and giving moringa leaves (p value = 0.034). Conclusions and Suggestions: There is a difference in the effect of giving oxytocin massage and giving Moringa leaves on breast milk production. It is hoped that breastfeeding mothers can consume processed Moringa leaves regularly during breastfeeding in order to increase breast milk production, besides that, families can motivate mothers in the process of breastfeeding by providing oxytocin massage so that mothers can breastfeed exclusively.